A study of factors affecting precision in atomic absorption spectrometry - Roos, Johannes Tielman Hofmeyr (Rhodes University, Faculty of Science, Department of Chemistry, 1976)
1. The effect of deviations from Beer's law on the precision of atomic absorption analysis has been examined from a theoretical point of view, and a function has been derived which makes it possible to evaluate quantitatively the effect of calibration curvature on the precision of analysis. The influence of incomplete sample volatilization on calibration curvature has been briefly investigated. 2. Possible error sources in atomic absorption spectrometry have been classified according to the "error function" (i.e., the dependence, upon transmittance T, of the uncertainty dT in a given transmittance measurement) with which they are associated. The magnitude of the contribution from each component function to the overall error function has been evaluated quantitatively, and it has been shown that the major component in nearly every case examined is that associated with the dynamic nature of the flame. Concentration ranges for optimum precision are suggested. 3. The effect of varying instrumental parameters on precision has been investigated, and generalized conditions for best precision have been ascertained. 4. The effect of an initial solvent extraction step on the precision of atomic absorption has been investigated for the elements copper and lead. It is shown that solvent extraction may be used to improve both the analytical sensitivity and the precision of analysis when very low concentrations of metal are determined. 5. The precision of analytical methods involving atomic absorption spectrometry has been studied, and the standard deviations compared with those obtained for the analysis of similar samples by means of a variety of other methods of analysis, both instrumental and classical.
Keywords: Atomic absorption spectroscopy